An approximate method to find changes in the blood flow characteristics in a larger coronary artery due to the appearance of its pathological tortuosity. A theory and experimental verification - Borysyuk, O.A. (Reports of the National Academy of Sciences of Ukraine, 2022)
An approximate method was developed to allow cardiologists to find (with acceptable precision and speed) both quantitative changes in the blood flow characteristics of interest in larger coronary arteries, caused by the appearance of their pathological tortuosity, and a hemodynamic significance of those changes based on the data taken from the appropriate coronary angiographies only. It is based on replacement of blood flows in the originally healthy and subsequently pathologically tortuous larger coronary artery with the appropriately averaged ones, and subsequent computation of the flows’ characteristics of interest in terms of the corresponding averaged flows’ characteristics. The method actually is non-invasive, allows one not to take account of a number of identical factors for the originally healthy and subsequently pathologically tortuous segment of the investigated artery, and gives one the possibility to determine the blood flow characteristics of concern at any time after carrying out a coronarography. In addition, it is not associated with solving complicated technical problems, and does not require special facility to be used, special professional training and significant financial and temporal expenses. The method was successfully tested in a laboratory experiment, after that recommended by cardiologists for the corresponding clinical application.